2012
DOI: 10.1155/2012/253497
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure over Height Ratios: Simple and Accurate Method of Detecting Elevated Blood Pressure in Children

Abstract: Background. Blood pressure (BP) percentiles in childhood are assessed according to age, gender, and height. Objective. To create a simple BP/height ratio for both systolic BP (SBP) and diastolic BP (DBP). To study the relationship between BP/height ratios and corresponding BP percentiles in children. Methods. We analyzed data on height and BP from 2006-2007 NHANES data. BP percentiles were calculated for 3775 children. Receiver-operating characteristic (ROC) curve analyses were performed to calculate sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
35
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 14 publications
10
35
1
Order By: Relevance
“…In the current study, the higher sensitivities and specificities of the BPHR in identifying HTN in comparison with pre-HTN were in agreement with previous studies and confirmed the better ability of the test for identifying hypertensives versus pre-hypertensives. Also, the higher sensitivity than specificity across all categories of HTN and pre-HTN in both sexes supported previous findings 12, 27,30,33,34 . This matches the purpose of this screening index, as it is desirable to have a low rate of false negative subjects who may miss diagnosis than to have a low rate of false positives who can be further excluded.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the current study, the higher sensitivities and specificities of the BPHR in identifying HTN in comparison with pre-HTN were in agreement with previous studies and confirmed the better ability of the test for identifying hypertensives versus pre-hypertensives. Also, the higher sensitivity than specificity across all categories of HTN and pre-HTN in both sexes supported previous findings 12, 27,30,33,34 . This matches the purpose of this screening index, as it is desirable to have a low rate of false negative subjects who may miss diagnosis than to have a low rate of false positives who can be further excluded.…”
Section: Discussionsupporting
confidence: 89%
“…These results were consistent with those of previous studies conducted in various countries 12,27,32 . However a relatively higher discriminating power has been documented in a previous study (ranging from 0.95 to 0.99) where authors have analysed all children with BP >90 th percentile for age and sex as one group, and didn't differentiate between pre-HTN and HTN 33 . The higher accuracy of the ROC curves in discriminating HTN compared to pre-HTN was similar to findings in similar studies, where AUC values increased with the degree of HTN in children and adolescents 24,30,34 .…”
Section: Discussionmentioning
confidence: 81%
“…These results are consistent with previous studies which stated that BPHR was not associated with age and height. 1,2,23,24 Thus, BPHR is simpler to use than the gold standard NHBPEP tables.…”
Section: Discussionmentioning
confidence: 99%
“…8 Thus, the need for a simple, inexpensive, and acceptable tool for detecting hypertension in children was urgent. The BPHR index was suggested as a simple and accurate index for identifying childhood hypertension in a local area of China 9 and has been replicated in Italian, 13 Nigerian, 14 US, 15 and Iranian children. 16 The BPHR index, standardized for height, is strongly and positively associated with SBP and DBP but is not related to age, so it is not dependent on height or age.…”
Section: Discussionmentioning
confidence: 99%